Diverse Roles of Macrophage Matrix Metalloproteinases in Tissue Destruction and Tumor Growth - Shapiro, Steven D. (Thrombosis and Haemostasis, 1999)
In the mouse, macrophage elastase is critical to macrophage proteolysis. The use of gene-targeting has uncovered both pathological roles, including destructive effects in aneurysm formation and emphysema, and physiological roles, such as tumor growth inhibition and regulation of inflammation. Translation of findings from mouse to human biology depends upon how well the disease models replicate the human conditions and the similarity of enzyme profile between species. We know that human MMP-12 is associated with these diseases, but as opposed to the mouse, other MMPs may also be of importance (MMP-9, and perhaps MMP-7, in particular). Our interpretation is that findings in mice reflect the critical role of macrophage proteolysis in these disease processes.